Divriği Hospital - Medieval Healing Venue and Its Acoustic Characteristics - Ivana Mihaljinec; Erdal Eser (Randwick International of Social Science Journal, 2022)
Divriği Great Mosque and Hospital as one of the World heritage monuments on UNESCO’s list was the subject of research. More precisely, the focus was on the architecture and the acoustic characteristics of the hospital built in 1228/1229 by Mengüjeck dynasty, a branch of Anatolian Seljuks. For the analysis purposes, a 3D model of the hospital was created, and the acoustic simulation was conducted. The results of the acoustic analysis show that the architectural characteristics of the hospital fulfill the acoustic standards for the good reception of the sound for the audience, and that it can be concluded that Divriği hospital venue supports the hypothesis of being suitable for the healing purposes. Hospital was designed to support the sound realization and to support the environmental soundscape in conjunction with the sounding makams, which supports the music therapy healing effect. It can be concluded that music therapy had acoustical support in the construction of Anatolian Seljuk hospitals, which have characteristics of concert halls and were built as acoustic (music) venues.